Does the genus Dasymutilla Ashmead occur in South America? The new genus Quwitilla, new combinations, and new distribution records from Neotropical velvet ants (Hymenoptera: Mutillidae) - Bartholomay, Pedro R.; Williams, Kevin A.; Cambra, Roberto. A.; Oliveira, Márcio L. (Zootaxa, 2019)
Nine species of the genus Dasymutilla Ashmead have been recorded from South America. One additional species, D. campogrande Manley & Pitts was erroneously recorded from Mexico but is from Brazil, and another species, D. colorado Cambra, Williams & Quintero was recently discovered in Colombia. Four of these nine Dasymutilla belong to a new genus, Quwitilla Williams, Bartholomay & Cambra, gen. nov., which includes: Q. peruviana (Suárez), comb. nov. (and its newly recognized female D. homochroma Suárez, syn. nov.; Q. bellatrix (Manley & Pitts), comb. nov. (based on female only); and Q. blattoserica (Kohl) comb. nov. (type species, already known from both sexes). Two others are actually synonyms of previously recognized Traumatomutilla André species: Dasymutilla brazilia Manley & Pitts, syn. nov. is a junior synonym of T. oculifera (Smith), and D. campogrande, syn. nov. is a junior synonym of T. inermis (Klug). One species is transferred out of Dasymutilla: Xystromutilla aequatorialis (André), comb. nov. Finally, updates and comments are provided on the distribution of D. araneoides (Smith), D. colorado, D. paradoxa (Gerstaecker), and D. pulchra (Smith), the only four South American species remaining in the genus Dasymutilla.